The deconstruction of the concept of political philosophy in Hannah Arendt's thinking (2009)
This article examines the ways in which Hannah Arendt deconstructs - or, as she says, dismantles - one fundamental assumption of the political and philosophical Western tradition: to believe in philosophy as a tool to solve political challenges. Arendt neither formulates a new normative political theory that may eventually be applicable in practice, nor does she regret the distance between philosophy and politics as if such a gap were a thinking flaw rather than a virtue of thought. Still, she seems to suggest that in political affairs no definite answers and solutions can be expected from promising theories elaborated by philosophers.